PENGARUH VARIASI METODE MENGAJAR GURU PAI TERHADAP MOTIVASI BELAJAR SISWA KELAS VIII SEMESTER GANJIL DI SMPS YPSA INTERNATIONAL SCHOOL T.P. 2019/2020 - sodri daulay (Universitas Islam Negeri Sumatera Utara Medan, 2020)
This research aims to: (1) Knowing the variety of teaching methods PAI teacher first semester of class VIII SMPS YPSA International School lessons 2019/2020, (2) knowing the learning motivation class VIII student of SMPS YPSA International School first semester year 2019/2020, (3) the effect of variations of PAI teacher teaching methods to motivate students of class VIII SMPS YPSA International School first semester year 2019/2020. In this research using quantitative descriptive, method product moment. The population of this research is class VIII SMPS YPSA International School numbering 49. After analyzing the data collected, it was found that: (1) the variation of teaching methods PAI teacher VIII SMPS YPSA International School is very good. (2) Motivation class VIII student of VIII SMPS YPSA International School is very good. (3) There is a variety of teaching methods influence on the motivation of teachers PAI class VIII student of VIII SMPS YPSA International School by 36.3%.